Electron self-exchange kinetics determined by MARY spectroscopy: theory and experiment. - Justinek, M; Grampp, G; Landgraf, S; Hore, P; Lukzen, N (2004)
The electron self-exchange between a neutral molecule and its charged radical, which is part of a spin-correlated radical ion pair, gives rise to line width effects in the fluorescence-detected MARY (magnetic field effect on reaction yield) spectrum similar to those observed in EPR spectroscopy. An increasing self-exchange rate (i.e., a higher concentration of the neutral molecule) leads to broadening and subsequent narrowing of the spectrum. Along with a series of MARY spectra recorded for several systems (the fluorophores pyrene, pyrene-d(10) and N-methylcarbazole in combination with 1,2- and 1,4-dicyanobenzene) in various solvents, a theoretical model is developed that describes the spin evolution and the diffusive recombination of the radical pair under the influence of the external magnetic field and electron self-exchange, thereby allowing the simulation of MARY spectra of the systems investigated experimentally. The spin evolution of the radicals in the pair is calculated separately using spin correlation tensors, thereby allowing rigorous quantum mechanical calculations for real spin systems. It is shown that the combination of these simulations with high resolution, low noise experimental spectra makes the MARY technique a novel, quantitative method for the determination of self-exchange rate constants. In comparison to a simple analytical formula which estimates the self-exchange rate constant from the slope of the linear part of a line width vs concentration plot, the simulation method yields more reliable and accurate results. The correctness of the results obtained by the MARY method is proved by a comparison with corresponding data from the well-established EPR line broadening technique. With its less stringent restrictions on radical lifetime and stability, the MARY technique provides an alternative to the classical EPR method, in particular for systems involving short-lived and unstable radicals.